The parts of speech classification principles in the works of main european grammarians - Zubenko, K. V.; Lazutkina, Yu. A.; Зубенко, K. В. (Видавничий дім «Гельветика», 2022)
The article represents basic principles of parts of speech classification in the works of main grammarians. Parts of speech are lexical-grammatical word classes characterized by a general abstract grammatical meaning expressed in certain grammatical markers. It means that within certain classes of words certain grammatical features are common to all words of the class.

У статті представлено основні принципи класифікації частин мови в працях відомих граматистів. Частини мови – це лексико-граматичні класи слів, що характеризуються загальним абстрактним граматичним значенням, вираженим певними граматичними ознаками. Це означає, що в певних класах слів певні граматичні ознаки є спільними для всіх слів класу.
Принципи класифікації частин мови в працях основних європейських граматистів
Keywords: part of speech; morphological principle; syntactic principle; logical principle; psychological principle; lexical and grammatical principle; cognitive principle; частина мови; морфологічний принцип; синтаксичний принцип; логічний принцип; психологічний принцип; лексико-граматичний принцип; когнітивний принцип